Evidence for DNA-PK-dependent and -independent DNA double-strand break repair pathways in mammalian cells as a function of the cell cycle. - Lee, S E (1997)
Mice homozygous for the scid (severe combined immune deficiency) mutation are defective in the repair of DNA double-strand breaks (DSBs) and are consequently very X-ray sensitive and defective in the lymphoid V(D)J recombination process. Recently, a strong candidate for the scid gene has been identified as the catalytic subunit of the DNA-dependent protein kinase (DNA-PK) complex. Here, we show that the activity of the DNA-PK complex is regulated in a cell cycle-dependent manner, with peaks of activity found at the G1/early S phase and again at the G2 phase in wild-type cells. Interestingly, only the deficit of the G1/early S phase DNA-PK activity correlated with an increased hypersensitivity to X-irradiation and a DNA DSB repair deficit in synchronized scid pre-B cells. Finally, we demonstrate that the DNA-PK activity found at the G2 phase may be required for exit from a DNA damage-induced G2 checkpoint arrest. These observations suggest the presence of two pathways (DNA-PK-dependent and -independent) of illegitimate mammalian DNA DSB repair and two distinct roles (DNA DSB repair and G2 checkpoint traversal) for DNA-PK in the cellular response to ionizing radiation.